1997
DOI: 10.1002/aic.690430806
|View full text |Cite
|
Sign up to set email alerts
|

Radial distribution of the flow velocity, efficiency and concentration in a wide HPLC column

Abstract: The use of optical fibers in a fluorescence-detection scheme permits the accurate determination of the radial distribution of the transit time, the column eficiency, and the analyte concentration at the exit of a chromatographic axialcompression column (50 mmID). The results obtained demonstrate that the column is not homogeneous, but suggest a nearly cylindrical distribution of the packing dens@. The average velocity close to the column wall is 7% lower than along its axis and the HETP 25% higher. The lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…18,21,43,44 In good packed columns, the linear velocity is slightly higher in the center than at the column wall ($3-7%). In monolithic columns, the opposite is true.…”
Section: Transcolumn Eddy Dispersionmentioning
confidence: 97%
“…18,21,43,44 In good packed columns, the linear velocity is slightly higher in the center than at the column wall ($3-7%). In monolithic columns, the opposite is true.…”
Section: Transcolumn Eddy Dispersionmentioning
confidence: 97%
“…It also demonstrates that the wall region of the column exhibits a greater tortuosity, as evidenced by the higher A values, and also a greater porosity, as evidenced by the smaller C values. Particle-packed columns that were previously studied [22] also exhibited a markedly heterogeneous radial distribution of the mobile phase velocity, around a fairly homogenous core. However, the mobile phase velocities in the wall region are lower than those in the core region [1,22], in contrast with what we observe for the monolithic column.…”
Section: Discussionmentioning
confidence: 97%
“…Particle-packed columns that were previously studied [22] also exhibited a markedly heterogeneous radial distribution of the mobile phase velocity, around a fairly homogenous core. However, the mobile phase velocities in the wall region are lower than those in the core region [1,22], in contrast with what we observe for the monolithic column. The effect is explained by a denser packing of the wall region due to the consequences of the heterogeneous distribution of the stress applied to the particles during the packing process and to their friction against the column wall.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The understanding of the effect of heterogeneous packing is a key to the improvement of large scale HPLC. Using on-column fluorescence-detection, Farkas et al found that at the exit of analytical HPLC columns, the mobile phase velocity profiles are nearly flat in the column center and falls rather rapidly towards the wall [12]; however, at the exit of an axial compression column (5 cm ID), the radial distributions of the velocity and the analyte concentration suggest a nearly parabolic distribution of the packing density [13]. The radial velocity distribution shown in Figure 4 in their work [13] is strongly curved and roughly parabolic.…”
Section: Introductionmentioning
confidence: 97%